(untitled) (Bangladesh Journal of Animal Science, 2012)
A study was conducted to determine the growth performance and mortality rate of Khaki Campell, Jinding and Deshi genotypes in two coastal locations of Barisal and Bhola districts of Bangladesh. Sixty-day-old ducks of 3 genotypes were randomly allocated to 3 treatments having 4 replications in each. Ducks are reared up to 150 days and at the end of experiment one male Khaki Campbell of highest live weight was selected from each replicate group. The average weekly body weight gain (g/bird) of the Khaki Campbell and Jinding were significantly (p<0.01) higher than those of the Deshi ducks. The average body weight of Khaki Campbell (1480.25g) was slightly higher than that of Jinding (1428.25g) but significantly (p<0.01) higher than that of Deshi (1140.62g) ducks at the end of the experiment. The mortality rate were significantly different (p<0.01) in various genotypes. The highest mortality was found in Deshi (30.20%) compared to Khaki Campbell (19.79%) and Jinding (17.77%). The profit margin was significantly different (p<0.01) in three genotypes. The ducks reared in Barishal performed better (p<0.01) than that from Bhola. It may be suggested from the present findings that both Khaki Campbell and Jinding ducks are performed better than Deshi in the coastal region of Bangladesh. http://dx.doi.org/10.3329/bjas.v41i1.11971